2009
DOI: 10.1093/hmg/ddp216
|View full text |Cite
|
Sign up to set email alerts
|

A common genetic variant in the 15q24 nicotinic acetylcholine receptor gene cluster (CHRNA5–CHRNA3–CHRNB4) is associated with a reduced ability of women to quit smoking in pregnancy

Abstract: Maternal smoking during pregnancy is associated with low birth weight and adverse pregnancy outcomes. Women are more likely to quit smoking during pregnancy than at any other time in their lives, but some pregnant women continue to smoke. A recent genome-wide association study demonstrated an association between a common polymorphism (rs1051730) in the nicotinic acetylcholine receptor gene cluster (CHRNA5–CHRNA3–CHRNB4) and both smoking quantity and nicotine dependence. We aimed to test whether the same polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
133
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 24 publications
10
133
1
2
Order By: Relevance
“…However, NRT is generally well tolerated at high doses, and in the studies reported here, there was no variation in dose offered. Moreover, this explanation is also not consistent with our failure to observe a differential effect in the placebo and active arms of the Patch II study and the effect of rs1051730 reported in other studies (Baker et al, 2009;Freathy et al, 2009;Thorgeirsson & Stefansson, 2010). A second possibility is that it might be associated with cessation because it influences heaviness of smoking or tobacco dependence.…”
Section: Discussioncontrasting
confidence: 83%
See 4 more Smart Citations
“…However, NRT is generally well tolerated at high doses, and in the studies reported here, there was no variation in dose offered. Moreover, this explanation is also not consistent with our failure to observe a differential effect in the placebo and active arms of the Patch II study and the effect of rs1051730 reported in other studies (Baker et al, 2009;Freathy et al, 2009;Thorgeirsson & Stefansson, 2010). A second possibility is that it might be associated with cessation because it influences heaviness of smoking or tobacco dependence.…”
Section: Discussioncontrasting
confidence: 83%
“…While our data on their own are inconclusive with respect to any association between variation in the CHRNA5-A3-B4 gene cluster and short-term smoking cessation in treatment-seeking smokers, it is notable that the magnitude of the effect we observed is consistent with recent evidence from a cohort study of pregnant women (Freathy et al, 2009), a community study of pregnant women (Thorgeirsson & Stefansson, 2010), and a clinical trial of treatment-seeking men and women (Baker et al, 2009). Taken together, these data are suggestive of a weak effect of genetic variation in this region on smoking cessation.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations